Efektivitas Kitosan Cangkang Kepiting sebagai Biokoagulan Mikroplastik Polistirena (PS) dalam Air Limbah - Afdal Ilahi; Indang Dewata (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the use of natural biocoagulants for microplastic removal, despite the significant environmental and human health impacts of this phenomenon. The aim of this research is to analyze the influence of pH variation, chitosan dosage, and settling time on the coagulation effectiveness of polystyrene (PS) microplastics, and to determine the process's optimum conditions. A quantitative method was employed, using PS microplastic solution samples (30 mg/L) treated under varying pH levels (4–10), chitosan doses (10–50 mg/L), and settling times (10–50 minutes). Data were collected through laboratory experiments and analyzed using Fourier Transform Infrared (FTIR) spectroscopy and stereo microscopy. The results indicate that optimum conditions were achieved at pH 6, with a chitosan dose of 30 mg/L and a settling time of 30 minutes, resulting in microplastic removal efficiency exceeding 90%. These findings support the theory of electrostatic interactions between the amine groups in chitosan and the negatively charged surface of microplastics. The main conclusion is that crab shell-derived chitosan is effective as an environmentally friendly biocoagulant for reducing microplastic content in wastewater. The study contributes to the growing literature on biocoagulation and offers practical recommendations for wastewater treatment managers to adopt sustainable natural coagulants. Moreover, it opens avenues for future research on chitosan-based composites for treating various types of microplastics.